IMPROVING LEARNING OUTCOMES THROUGH TWO STAY TWO STRAY COOPERATIVE LEARNING - Irianti, Irianti; admin, admin (Publikasi dan UKI Press UKI Toraja., 2022)
The main challenge of this research is how to use the Type Two Stay Two Stray cooperative learning approach with a total of 28 students—14 boys and 14 girls in SD Plus Al-Ashri to improve learning outcomes. Four meetings were held during each of the two research cycles this was conducted. Observation sheets and academic achievement tests were used to obtain data. Quantitative and qualitative analysis of collected data. The results showed that quantitatively the learning outcomes of had increased, namely the average score of student learning outcomes in cycle I was 57.92 , and the percentage of students in the high category was 7.14%, while the average score was 7.14%. Student learning outcomes in cycle II amounted to 80.53, the high proportion of sub-students was 35.71%. In cycle I there were 7 students or 25% in the complete category and 21 students or 75% in the incomplete category, while in cycle II there were 27 students or 96.42% in the complete category and 1 student or 3.57% in the complete category. incomplete category implies an increase from period I to period II. Qualitatively, during the learning process, the enthusiasm of students to listen to lectures, the enthusiasm to pay attention to the teacher's explanation, the enthusiasm to ask questions, and their active role in the learning process when completing homework in groups experienced changes. The increase in the first cycle was 36.80 %, and the increase in the second cycle was 40.68%. Based on the results of the analysis it can be concluded that the learning outcomes of students at SD Plus Al-Ashri can be improved by using the Type Two Stay Two Stray (TSTS) cooperative learning model.